Isolated Asymptomatic Metastasis in the Myocardium: A Rare Scenario in Case of Carcinoma Penis - Kumar,Santosh; Parmar,Kalpesh Mahesh; Singh,Shivanshu; Kumar,Jayant
Penile cancer is a common malignancy in developing countries. It commonly metastasizes to the lymph nodes, lung, liver, and bones. Myocardial metastasis is rare. A 40-year-old male patient presented with ulcerative growth over glans penis. Histologic evaluation of the biopsy sample diagnosed the lesion as squamous cell cancer. Assessment of the stage of the disease revealed cardiac metastasis. Patient received six cycles of chemotherapy. He partially responded, but later succumbed to cardiac failure due to pericardial and pleural effusion.